Implementation of a streamlined prior authorization process to improve clinician wellness and cancer care delivery. Issue 28 (1st October 2022) - Bhardwaj, Aarti Sonia; Pintova, Sofya; Liu, Mark; Noble-Kirk, Alana; Blunck, Peter; Smith, Cardinale B.
Abstract : 428 Background: Prior authorizations (PAs) for chemotherapy are increasingly becoming a barrier to timely and quality care delivery for cancer patients. There is an extraordinary administrative burden placed on clinical teams to participate in peer to peers (P2P) and file appeals when authorization specialists are unable to efficiently find the necessary clinical data in the EHR. 1 This leads to delays in care, staff burnout driven by decreased job satisfaction, loss of revenue from decreased clinician productivity and from chemotherapy given emergently but not retroactively reimbursed. 2 In partnership with the cancer registry team and Epic, we propose a workflow that shifts the clerical work required for PAs from the clinical teams to the certified tumor registrars (CTRs) using smart form optimization so the finance team has all the required information in one place to successfully and efficiently process the PAs. Methods: A list of common data elements including performance status, cancer biomarkers, line of treatment, goals of treatment and stage were identified. We are leveraging the staging smart form in EPIC to auto-populate these elements when available and then use CTRs to enter cancer stage, fill in any gaps and validate the data. Once approved by the CTR, the chemotherapy plan will be available in the authorization work queue for efficient processing. In 2020, we had 1, 389 chemotherapy plans entered and about 38% of these required clinical intervention for financial clearance. We will track the number of P2Ps being conducted post-implementation and compare this to numbers prior to implementation. We will use descriptive statistics and t-test to compare these values. We are anticipating a 25% decrease in P2Ps. We will survey oncology physicians in June 2022 to measure baseline perceived physician impact of PAs and burnout and then again in January 2023 to measure the impact post-implementation. Results: A wellness survey was administered to Medical Oncology faculty within the Mount Sinai Health System pre-pandemic in 2020 and in 2021 and among respondents, approximately 1/3 have moderate to severe burnout risk pre- and post-pandemic. Coordination of care and PAs were rated as the largest barriers to wellbeing, and this increased from 43% pre- to 71% post-pandemic indicating a significant area of opportunity to improve wellbeing among medical oncology faculty. Conclusions: By leveraging technology and non-clinical staff workflows to improve the processing of insurance PAs of ambulatory intravenous chemotherapy, we aim to improve timeliness of quality care delivery to patients and clinical staff wellness. West CP et.al. Physician burnout: contributors, consequences and solutions. J Intern Med. Jun 2018;283(6):516-529. Lin NU et al. Increasing Burden of Prior Authorizations in the Delivery of Oncology Care in the United States. J Oncol Pract. Sep 2018;14(9):525-528.